Assessment of the application for renewal of authorisation of 6‐phytase produced by Trichoderma reeseiCBS 122001 as a feed additive for pigs and poultry, from Roal Oy. (15th December 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Pechová, Alena; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the assessment of the application for renewal of authorisation of 6‐phytase produced by Trichoderma reesei CBS 122001 (brand name: Finase ® EC). The applicant has provided evidence that the additive currently in the market complies with the existing conditions of authorisation. The Panel concludes that the additive remains safe for poultry for fattening, breeding and laying, and all pigs, the consumer and the environment under the authorised conditions of use. Regarding user safety, the Panel reiterates that the additive is not a skin or eye irritant or sensitiser but should be considered a potential respiratory sensitiser. There is no need for assessing the efficacy of the additive in the context of the renewal of the authorisation. These conclusions also apply to the new proposed liquid formulation Finase ® EC 5 L.